Turmeric, red pepper, and black pepper affect carotenoids solubilized micelles properties and bioaccessibility: Capsaicin/piperine improves and curcumin inhibits carotenoids uptake and transport in Caco‐2 cells. Issue 11 (17th October 2021) - Shilpa, Shivaprasad; Shwetha, Hulikere Jagdish; Perumal, Madan Kumar; Ambedkar, Rudrappa; Hanumanthappa, Manjunatha; Baskaran, Vallikannan; Lakshminarayana, Rangaswamy
Abstract : Abstract: This study aimed to evaluate the role of spices/spice active principles on physical, biochemical, and molecular targets of bioaccessibility/bioavailability. Carotenoids‐rich micellar fraction obtained through simulated digestion of green leafy vegetables (GLV) with individual or two/three combinations were correlated to their influence on bioaccessibility, cellular uptake, and basolateral secretion of carotenoids in Caco‐2 cells. Results suggest that carotenoids' bioaccessibility depends on micelles physicochemical properties, which is affected due to the presence of co‐treated dietary spices and their composition. Increased bioaccessibility of β‐carotene (BC) and lutein (LUT) is found in GLV (spinach) digested with turmeric (TM) than red pepper (RP) and black pepper (BP). In contrast, enhanced cellular uptake and secretion of BC and LUT‐rich triglyceride‐rich lipoprotein is observed in the presence of RP and BP compared to the control group. In contrast, TM inhibited absorption, while retinol levels significantly reduced in the presence of TM and RP than BP. Control cells have indicated higher cleavage of β‐carotene to retinol than the spice‐treated group. Besides, spice active principles modulate facilitated transport of carotenoids by scavenger receptor class B type 1 (SR‐B1) protein. The effect of spices on carotenoids' bioavailability is validated with active spice principles. Overall, carotenoids' bioavailability (cellular uptake and basolateral secretion) was found in the following order of treatments; piperine > capsaicin > piperine + capsaicin > curcumin + capsaicin + piperine > control > turmeric. These findings suggested that the interaction of specific dietary factors, including spice ingredients at the enterocyte level, could provide greater insight into carotenoid absorption. Practical Application: Spices/spice active principles play a role in the digestion process by stimulating digestive enzymes and bile acids secretion. Since carotenoids are lipid soluble and have low bioavailability, spice ingredients' influence on intestinal absorption of carotenoids is considered crucial. Hence, understanding the interaction of co‐consumed spices on the absorption process of carotenoids may help to develop functional foods/formulation of nutraceuticals to improve their health benefits.